Reading Dar es Salaam's (Female-led) Book Clubs as Paravirtual Networks. Issue 1 (3rd April 2021) - Geuza, Zamda R.; Wallis, Kate
ABSTRACT: This article focuses on three Dar es Salaam-based book clubs, all founded by women post-2016 – Taswira Book Club, Umoja Book Club and Leaders Read Book Club – and examines how they are positioned through their relationships with booksellers, digital technology and each other. Building on the work of Stephanie Bosch-Santana and drawing on original interview material, it argues for these book clubs as paravirtual networks through which vibrant reading communities are being constructed in Tanzania. Documenting the variety of ways in which digital technology supports and sustains these new literary communities, even while physical meetings continue to be important, this article is concerned with how these book clubs are able to open up new forms of social space and female-led communal participation around books. While booksellers in Tanzania are working closely with these book clubs, this study reveals a disconnect between these book clubs and Tanzania-based publishers. The conclusion proposes that new modes of literary activism can be opened up by publishers and book clubs working more closely together.